Solid-state lithium ion battery and preparation method thereof

By using composite lithium element as the negative electrode active material, combined with specific battery structures and preparation methods, the problem of insufficient capacity and susceptibility to the environment in solid-state lithium-ion batteries is solved, and the battery performance with high energy density and long cycle life is achieved.

CN119601744APending Publication Date: 2025-03-11广东科信聚力新能源有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411662013.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The negative electrode active materials of existing solid-state lithium-ion batteries have low capacity, which is difficult to meet the needs of high energy density and long cycle life. They are also susceptible to air and water vapor, affecting the service life of the battery.

Method used

Composite lithium element is used as the negative electrode active material. Composite lithium element is composed of lithium element layer, lithium carbonate layer, carbon clad layer and solid electrolyte phase interface film to reduce reaction with air and water vapor, and to improve the stability and life of the battery through specific battery structures and preparation methods.

Benefits of technology

It improves the service life of solid-state lithium-ion batteries, reduces the impact on air and water vapor, meets the needs of high energy density and long cycle life, and simplifies the battery preparation process and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601744A_ABST
    Figure CN119601744A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a solid-state lithium ion battery and a preparation method thereof. The positive plate and the negative plate are arranged in the shell and are wound or laminated; the positive plate comprises an aluminum foil, and a carbon coating layer, a positive electrode material layer and a positive electrode solid electrolyte layer which are sequentially arranged on each side of the aluminum foil from inside to outside; the negative plate comprises a copper foil, and a negative electrode material layer and a negative electrode solid electrolyte layer which are sequentially arranged on each side of the copper foil from inside to outside; the negative electrode material layer comprises a negative electrode active material, the negative electrode active material comprises a composite lithium elementary substance, and the composite lithium elementary substance comprises a lithium elementary substance layer, a lithium carbonate layer, a carbon coating layer and a solid electrolyte phase interface film which are sequentially arranged from inside to outside.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a solid-state lithium ion battery and a preparation method thereof. Background Art

[0002] With the development of current technology, lithium-ion batteries are widely used in electronic equipment and electric vehicle lighting. However, traditional liquid lithium-ion batteries have problems in terms of safety and energy density. Solid-state lithium-ion batteries have higher safety and potential higher energy density due to the use of solid electrolytes.

[0003] In the negative electrode sheets of existing solid-state lithium batteries, the negative electrode active materials are mostly carbon-based compounds. The disadvantage of this material is that the capacity of carbon-based materials is low and cannot meet the needs of high energy density and long cycle life. In addition, the negative electrode active materials are easily affected by air and water vapor, causing reactions and affecting the service life of lithium batteries.

[0004] In addition, the current preparation methods of solid-state batteries generally use dry and wet processes. The wet process is to dissolve the polymer (PEO, etc.) in a solvent (NMP), and then add lithium salt (LiTFSI), plasticizer and inert filler to prepare the electrolyte slurry. The electrolyte slurry is formed into a film by solution casting or doctoring, and then heated and dried to solidify the polymer and evaporate the solvent to form a polymer electrolyte film.

[0005] The dry process is to melt the positive electrode and electrolyte slurry at high temperature to form a high-viscosity paste, and then mix and extrude it on the positive electrode current collector at the same time, and compact it through a roll press. After the negative electrode is coated, the multi-layer battery cell is compacted through a roller valve. The process of these two processes is complex and has high requirements for equipment, making it difficult to apply them on a large scale in the terminal. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a solid-state lithium-ion battery cell, which reduces the impact of air and water vapor on the battery cell and increases the service life of the battery cell.

[0007] The present invention also provides a solid-state lithium-ion battery. By using the solid-state lithium-ion battery, the solid-state lithium-ion battery has a long service life.

[0008] Another object of the present invention is to provide a method for preparing a solid-state lithium-ion battery, which solves the problem that the lithium-ion battery manufacturing process is complicated, has high requirements for equipment and environment, and is difficult to be applied on a large scale in terminals.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] A solid-state lithium-ion battery, comprising:

[0011] shell;

[0012] A positive electrode sheet and a negative electrode sheet arranged in a wound or laminated manner in the housing;

[0013] The positive electrode sheet comprises an aluminum foil, and a carbon coating layer, a positive electrode material layer and a positive electrode solid electrolyte layer are sequentially arranged from the inside to the outside on each side of the aluminum foil;

[0014] The negative electrode sheet comprises a copper foil, and a negative electrode material layer and a negative electrode solid electrolyte layer are sequentially arranged from the inside to the outside on each side of the copper foil;

[0015] The negative electrode material layer includes a negative electrode active material, the negative electrode active material includes a composite lithium element, and the composite lithium element includes a lithium element layer, a lithium carbonate layer, a carbon coating layer and a solid electrolyte phase interface film arranged in sequence from the inside to the outside.

[0016] Preferably, the positive electrode material layer includes a uniformly mixed positive electrode active material and a first solid electrolyte, and the negative electrode material layer also includes a second solid electrolyte;

[0017] The size range of the particle size D50 of the material particles of the first solid electrolyte and the second solid electrolyte is 0.5 μm to 10 μm;

[0018] The ratio of the particle size D50 of the material particles of the first solid electrolyte to the particle size D50 of the material particles of the positive electrode active material is in the range of 1:2-1:5;

[0019] The ratio of the particle size D50 of the material particles of the second solid electrolyte to the particle size D50 of the material particles of the negative electrode active material is in the range of 1:2-1:5.

[0020] Preferably, the positive electrode solid electrolyte layer includes a third solid electrolyte, the negative electrode solid electrolyte layer includes a fourth solid electrolyte, and the material particle size D50 of the third solid electrolyte and the fourth solid electrolyte are both in the range of 0.5 μm to 10 μm.

[0021] Preferably, the porosity of the positive electrode material layer, the negative electrode material layer, the positive electrode solid electrolyte layer and the negative electrode solid electrolyte layer are all less than 30%.

[0022] As a preference,

[0023] The positive electrode material layer further includes a first conductive agent and a first adhesive, and the mass ratio of the positive electrode active material, the first solid electrolyte, the first conductive agent and the first adhesive is in the range of (93wt% to 96wt%): (2wt% to 5wt%): (1wt% to 3wt%): (2wt% to 3wt%);

[0024] And / or, the negative electrode active material further includes a second conductive agent and the second binder, and the mass ratio of the negative electrode active material, the second solid electrolyte, the second conductive agent and the second binder is (93wt% to 96wt%): (2wt% to 5wt%): (1wt% to 3wt%): (2wt% to 3wt%);

[0025] And / or, the positive electrode solid electrolyte layer further includes a third adhesive, and the mass ratio of the third solid electrolyte to the third adhesive is in the range of (95wt% to 98wt%): (2wt% to 5wt%);

[0026] And / or, the negative electrode solid electrolyte layer further includes a fourth adhesive, and the mass ratio of the fourth solid electrolyte to the fourth adhesive is in the range of (95wt% to 98wt%): (2wt% to 5wt%).

[0027] Preferably, the thickness of the aluminum foil ranges from 10 μm to 13 μm;

[0028] The thickness of the carbon coating layer ranges from 0.5 μm to 1 μm;

[0029] The thickness of the positive electrode material layer ranges from 150 μm to 250 μm;

[0030] The material surface density of the positive electrode material layer is 150g / ㎡-220g / ㎡;

[0031] The thickness of the positive electrode solid electrolyte layer is 5 μm to 10 μm; the thickness of the negative electrode solid electrolyte layer is 5 μm to 10 μm;

[0032] The NP ratio of the solid-state lithium-ion battery ranges from 1.05 to 1.15.

[0033] Preferably, the positive electrode material layer, the negative electrode material layer, the positive electrode solid electrolyte layer and the negative electrode solid electrolyte layer all include a liquid electrolyte with a mass ratio of 1-5 wt%.

[0034] Preferably, the positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich layered oxide;

[0035] The negative electrode active material also includes at least one of graphite, lithium titanate, silicon carbon, silicon oxygen, hard carbon, and soft carbon;

[0036] The carbon coating layer, the first conductive agent and the second conductive agent include at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fibers and carbon black;

[0037] The first adhesive, the second adhesive, the third adhesive and the fourth adhesive all include at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyacrylate, nitrile rubber and styrene-butadiene rubber;

[0038] The positive electrode active material layer further includes a first solvent, the negative electrode active material layer further includes a second solvent, the positive electrode solid electrolyte layer further includes a third solvent, and the negative electrode solid electrolyte layer further includes a fourth solvent, the first solvent, the third solvent and the fourth solvent are all N-methylpyrrolidone, and the second solvent is deionized water;

[0039] The first solid electrolyte, the second solid electrolyte, the third solid electrolyte and the fourth solid electrolyte each include at least one of a halide solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte and a polymer electrolyte.

[0040] The present invention also provides a method for preparing a solid-state lithium-ion battery cell, comprising:

[0041] S1, coating the carbon material on the aluminum foil to form a carbon coating layer;

[0042] Applying a positive electrode active mixed slurry on the carbon coating layer to form a positive electrode material layer;

[0043] Applying a positive electrode solid electrolyte slurry on the positive electrode material layer to form a positive electrode solid electrolyte layer to obtain a positive electrode sheet;

[0044] S2, coating the negative electrode active mixed slurry containing composite lithium element on the copper foil to form a negative electrode material layer;

[0045] Applying a negative electrode solid electrolyte slurry on the negative electrode material layer to form a negative electrode solid electrolyte layer, and obtaining a negative electrode sheet;

[0046] S3, rolling, slitting, winding or laminating the positive electrode sheet and the negative electrode sheet to form a battery cell;

[0047] S4, the battery cell is installed in a housing to form a battery;

[0048] S5. Inject liquid electrolyte into the battery, and evacuate the battery and seal it.

[0049] Preferably, the vacuum degree of the battery in S5 is not greater than -85 kPa, and the vacuuming time is 30 s-120 s.

[0050] Compared with the prior art, the present invention has the following beneficial effects: in the present invention, the aluminum foil is used as the current collector of the positive electrode sheet, and the carbon coating layer, the positive electrode material layer, and the positive electrode solid electrolyte layer are sequentially coated on both sides of the aluminum foil. The negative electrode active material of the negative electrode material layer includes a composite lithium single substance, and the composite lithium single substance is a lithium single substance layer, a lithium carbonate layer, a carbon coating layer, and a solid electrolyte phase interface film from the inside to the outside. The lithium single substance layer is coated with an inert material, is not easy to react with air and water vapor, is less affected by the environment, and is easy to be mixed with NMPP solvent and adhesive into slurry for coating. The solid-state lithium battery formed is less affected by external air and water vapor, and the solid-state lithium battery has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 It is a schematic diagram of the structure of the positive electrode sheet in the present invention;

[0052] Figure 2 It is a schematic diagram of the structure of the negative electrode sheet in the present invention;

[0053] Figure 3 It is a schematic diagram of the structure of the composite lithium single substance in the present invention.

[0054] Among them, 1. positive electrode sheet; 11. aluminum foil; 12. carbon coating layer; 13. positive electrode material layer; 14. positive electrode solid electrolyte layer; 2. negative electrode sheet; 21. copper foil; 22. negative electrode material layer; 23. negative electrode solid electrolyte layer; 3. composite lithium single substance; 31. lithium single substance layer; 32. lithium carbonate layer; 33. carbon coating layer; 34. solid electrolyte phase interface film. DETAILED DESCRIPTION

[0055] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0056] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0057] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0058] In the description of the present invention, it should be noted that the terms "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or are the positions or positional relationships in which the inventive product is usually placed when in use. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0059] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "disposed" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0060] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0061] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0062] like Figure 1-Figure 3As shown, a solid-state lithium-ion battery is provided in this embodiment, including a shell, and a positive electrode sheet 1 and a negative electrode sheet 2 arranged in a wound or laminated manner in the shell. Among them, the positive electrode sheet 1 includes an aluminum foil 11, and a carbon coating layer 12, a positive electrode material layer 13 and a positive electrode solid electrolyte layer 14 are sequentially arranged from the inside to the outside on each side of the aluminum foil 11. The negative electrode sheet 2 includes a copper foil 21, and a negative electrode material layer 22 and a negative electrode solid electrolyte layer 23 are sequentially arranged from the inside to the outside on each side of the copper foil 21. The negative electrode material layer 22 includes a negative electrode active material, and the negative electrode active material includes a composite lithium single substance 3, and the composite lithium single substance 3 includes a lithium single substance layer 31, a lithium carbonate layer 32, a carbon coating layer 33 and a solid electrolyte phase interface film 34 sequentially arranged from the inside to the outside. The above-mentioned aluminum foil 11 and the positive electrode ear are electrically conductive by welding; the copper foil 21 and the negative electrode ear are electrically conductive by welding.

[0063] In this embodiment, the aluminum foil 11 is used as the current collector of the positive electrode sheet 1, and the carbon coating layer 12, the positive electrode material layer 13, and the positive electrode solid electrolyte layer 14 are sequentially coated on both sides of the aluminum foil 11. The negative electrode active material of the negative electrode material layer 22 includes a composite lithium single substance 3, which is a lithium single substance layer 31, a lithium carbonate layer 32, a carbon coating layer 33 and a solid electrolyte phase interface film 34 from the inside to the outside. The lithium single substance layer 31 is coated with an inert material, is not easy to react with air and water vapor, is less affected by the environment, and is easily mixed with NMPP solvent and adhesive to form a slurry for coating. The solid-state lithium battery formed is less affected by external air and water vapor, and the solid-state lithium battery has a long service life.

[0064] Preferably, with respect to the specific structure of the positive electrode sheet 1, the positive electrode material layer 13 of the positive electrode sheet 1 includes a uniformly mixed positive electrode active material, a first solid electrolyte, a first conductive agent, and a first adhesive. The mass ratio of the positive electrode active material, the first solid electrolyte, the first conductive agent, and the first adhesive is in the range of (93wt% to 96wt%): (2wt% to 5wt%): (1wt% to 3wt%): (2wt% to 3wt%).

[0065] The specific structure of the negative electrode sheet 2 is that the negative electrode material layer 22 of the negative electrode sheet 2 includes not only the negative electrode active material, but also a second solid electrolyte, a second conductive agent, and a second adhesive. The mass ratio of the negative electrode active material, the second solid electrolyte, the second conductive agent, and the second adhesive is: (93wt% to 96wt%): (2wt% to 5wt%): (1wt% to 3wt%): (2wt% to 3wt%). Specifically, the composite lithium element 3 is evenly mixed with the second solid electrolyte, the second conductive agent, and the second adhesive, and then coated on the copper foil 21 to form the negative electrode material layer 22.

[0066] The positive electrode solid electrolyte layer 14 includes a third solid electrolyte and a third adhesive. The mass ratio of the third solid electrolyte to the third adhesive is in the range of (95wt% to 98wt%): (2wt% to 5wt%). The third solid electrolyte and the third adhesive are evenly mixed and evenly coated on the positive electrode material layer 13 to form the positive electrode solid electrolyte layer 14.

[0067] And / or, the negative electrode solid electrolyte layer 23 includes a fourth solid electrolyte and a fourth adhesive, and the mass ratio of the fourth solid electrolyte to the fourth adhesive is in the range of (95wt% to 98wt%): (2wt% to 5wt%). The fourth solid electrolyte and the fourth adhesive are uniformly mixed and then uniformly coated on the negative electrode material layer 22 to form the negative electrode solid electrolyte layer 23.

[0068] The size range of the particle size D50 of the material particles of the first solid electrolyte and the second solid electrolyte is 0.5 μm to 10 μm.

[0069] The particle size D50 of the material particles of the third solid electrolyte and the fourth solid electrolyte is in the range of 0.5 μm to 10 μm.

[0070] The ratio of the particle size D50 of the material particles of the first solid electrolyte to the particle size D50 of the material particles of the positive electrode active material is in the range of 1:2-1:5.

[0071] The ratio of the particle size D50 of the material particles of the second solid electrolyte to the particle size D50 of the material particles of the negative electrode active material is in the range of 1:2-1:5.

[0072] The particle size of the material particles of the above-mentioned first solid electrolyte is smaller than that of the material particles of the positive electrode active material, and the particle size of the material particles of the second solid electrolyte is smaller than that of the material particles of the negative electrode active material. Therefore, the first solid electrolyte can better fill the gaps between the positive electrode active materials, and the second solid electrolyte can better fill the gaps between the negative electrode active materials, so that the particles are in close contact and the migration performance of ions is enhanced.

[0073] The liquid electrolyte in this embodiment includes lithium salt and organic solvent. The lithium salt, such as lithium hexafluorophosphate LiPF6, is the main conductive component, which provides ions with positive and negative charges to make the electrolyte conductive. The organic solvent includes propylene carbonate and dimethyl carbonate, which is responsible for dissolving the lithium salt and providing an environment conducive to the movement of ions.

[0074] For each layer structure of the positive electrode sheet 1, the thickness of the aluminum foil 11 is in the range of 10μm-13μm. The thickness of the carbon coating layer 12 is in the range of 0.5μm-1μm. The thickness of the positive electrode material layer 13 is in the range of 150μm-250μm. The material surface density of the positive electrode material layer 13 is 150g / ㎡-220g / ㎡. The thickness of the positive electrode solid electrolyte layer 14 is 5μm-10μm; the thickness of the negative electrode solid electrolyte layer 23 is 5μm-10μm. The NP ratio of the solid-state lithium-ion battery ranges from 1.05 to 1.15.

[0075] Preferably, the first solid electrolyte, the second solid electrolyte, the third solid electrolyte and the fourth solid electrolyte all include at least one of a halide solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte and a polymer electrolyte. The first solid electrolyte, the second solid electrolyte, the third solid electrolyte and the fourth solid electrolyte can be the same or different. And the first solid electrolyte, the second solid electrolyte, the third solid electrolyte and the fourth solid electrolyte are one of the halide solid electrolyte, the sulfide solid electrolyte, the oxide solid electrolyte and the polymer electrolyte or a mixture of at least two of them.

[0076] Preferably, the carbon coating layer 12 includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fibers, and carbon black.

[0077] Preferably, the positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich layered oxide. The positive electrode active material can be one of the above materials, or a mixture of at least two of them.

[0078] Preferably, the negative electrode active material further comprises at least one of graphite, lithium titanate, silicon carbon, silicon oxygen, hard carbon, and soft carbon. The negative electrode active material in this embodiment comprises a composite lithium element 3, or the negative electrode active material is a mixture, specifically comprising a composite lithium element 3, and further comprising at least one of graphite, lithium titanate, silicon carbon, silicon oxygen, hard carbon, and soft carbon.

[0079] Preferably, the first conductive agent and the second conductive agent both include at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fiber, and carbon black. The first conductive agent and the second conductive agent can be the same or different. The first conductive agent and the second conductive agent can be one of the above materials, or a mixture of at least two of them.

[0080] Preferably, the first adhesive, the second adhesive, the third adhesive and the fourth adhesive all include at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyacrylate, nitrile rubber and styrene-butadiene rubber.

[0081] The first adhesive and the second adhesive, the third adhesive and the fourth adhesive may be different from each other, or may be the same.

[0082] The positive electrode material layer 13 further includes a first solvent, which is an N-methylpyrrolidone solvent. The negative electrode material layer 22 further includes a second solvent, which is deionized water. Specifically, in this embodiment, the positive electrode material layer 13 includes a uniformly mixed positive electrode active material, a first solid electrolyte, a first conductive agent, a first adhesive, and a first solvent. The negative electrode material layer 22 includes a uniformly mixed negative electrode active material, a second solid electrolyte, a second conductive agent, a second adhesive, and a second solvent.

[0083] Preferably, the positive electrode solid electrolyte layer 14 further includes a third solvent, and the negative electrode solid electrolyte layer 23 further includes a fourth solvent, and the third solvent and the fourth solvent are both N-methylpyrrolidone solvent. Specifically, in this embodiment, the positive electrode solid electrolyte layer 14 includes a third solid electrolyte, a third adhesive, and a third solvent that are mixed evenly. The negative electrode solid electrolyte layer 23 includes a fourth solid electrolyte, a fourth adhesive, and a fourth solvent that are mixed evenly.

[0084] Preferably, the positive electrode material layer 13, the negative electrode material layer 22, the positive electrode solid electrolyte layer 14 and the negative electrode solid electrolyte layer 23 all include a liquid electrolyte with a mass ratio of 1-5 wt%.

[0085] The above-mentioned liquid electrolyte is simultaneously present in the positive electrode material layer 13, the negative electrode material layer 22, the positive electrode solid electrolyte layer 14 and the negative electrode solid electrolyte layer 23. Because there are gaps between the material particles of the positive electrode material layer 13 and the negative electrode material layer 22, the liquid electrolyte exists in the gap in a free form. Similarly, there are gaps between the material particles of the third solid electrolyte and the material particles of the fourth solid electrolyte, and the liquid electrolyte exists in the gap in a free form. Further preferably, the liquid electrolyte enters the positive electrode material layer 13, the negative electrode material layer 22, the positive electrode solid electrolyte layer 14 and the negative electrode solid electrolyte layer 23 through an infiltration process. During the charge and discharge process of the solid-state battery, therefore, the stability of the contact interface between the particles is ensured by the liquid electrolyte, thereby increasing the transmission path of ions and electrons, ensuring that the positive electrode active material and the negative electrode active material will not cause the transmission path of electrons and ions to be interrupted during expansion and contraction, maintaining the stability of the charge and discharge operation, and also improving the service life of the battery.

[0086] There is a liquid electrolyte in the first solid electrolyte, the second solid electrolyte, the positive electrode solid electrolyte layer and the negative electrode solid electrolyte layer. The presence of the liquid electrolyte increases the ion concentration and promotes the movement of ions under the action of the electric field, thereby improving the conductivity. By adding a small amount of liquid electrolyte to the first solid electrolyte, the second solid electrolyte, the positive electrode solid electrolyte layer 14 and the negative electrode solid electrolyte layer 23, the conductivity and wettability of the battery can be improved.

[0087] Preferably, the porosity of the positive electrode material layer 13 , the negative electrode material layer 22 , the positive electrode solid electrolyte layer 14 and the negative electrode solid electrolyte layer 23 are all less than 30%.

[0088] Because the positive electrode material layer 13 is formed by mixing the positive electrode active material, the first solid electrolyte, the first binder, the first conductive agent and the first solvent. The negative electrode material layer 22 is formed by mixing the negative electrode active material, the second solid electrolyte, the second binder, the second conductive agent and the second solvent, the positive electrode material layer 13 and the negative electrode material layer 22 are both composite materials. And because the negative electrode active material is a composite lithium single substance 3, the periphery of the composite lithium single substance 3 is coated with a solid electrolyte phase interface film 34, and the stability of the battery structure is further enhanced.

[0089] This embodiment also provides a method for preparing a solid-state lithium-ion battery cell, comprising:

[0090] S1, coating a carbon material on an aluminum foil 11 to form a carbon coating layer 12;

[0091] The positive electrode active mixed slurry is coated on the carbon coating layer 12 to form a positive electrode material layer 13;

[0092] The positive electrode solid electrolyte slurry is coated on the positive electrode material layer 13 to form a positive electrode solid electrolyte layer 14, thereby obtaining a positive electrode sheet 1;

[0093] S2, coating the negative electrode active mixed slurry containing the composite lithium element 3 on the copper foil 21 to form a negative electrode material layer 22;

[0094] The negative electrode solid electrolyte slurry is coated on the negative electrode material layer 22 to form a negative electrode solid electrolyte layer 23, and a negative electrode sheet 2 is obtained;

[0095] S3, rolling, slitting, winding or laminating the positive electrode sheet 1 and the negative electrode sheet 2 to form a battery cell;

[0096] S4, the battery cell is installed in the housing to form a battery;

[0097] S5. Inject liquid electrolyte into the battery, evacuate the battery and seal it.

[0098] In the preparation method of the solid-state lithium-ion battery in this embodiment, the positive electrode active mixed slurry is coated on the carbon-coated layer 12 to form the positive electrode material layer 13, and the positive electrode solid electrolyte slurry is coated on the positive electrode material layer 13 to form the positive electrode solid electrolyte layer 14, and the positive electrode sheet 1 is obtained. Similarly, the negative electrode active mixed slurry containing the composite lithium element 3 is coated on the copper foil 21 to form the negative electrode material layer 22, and the negative electrode solid electrolyte slurry is coated on the negative electrode material layer 22 to form the negative electrode solid electrolyte layer 23, and the negative electrode sheet 2 is obtained. Then, the battery is assembled in a stacking or winding manner, and after the battery is assembled with the shell, the liquid electrolyte is injected into the interior and then packaged to form a battery. The manufacturing process is simple, easy to implement, and has low requirements for processing equipment, so the production cost is also low.

[0099] Preferably, step S1 also includes:

[0100] S11, mixing a positive electrode active material, a first solid electrolyte, a first conductive agent, a first adhesive, and a first solvent according to a first predetermined ratio to form a positive electrode active mixed slurry;

[0101] The third solid electrolyte, the third binder and the third solvent are mixed in a third predetermined ratio to form a positive electrode solid electrolyte slurry.

[0102] Preferably, step S1 also includes:

[0103] S12, the positive electrode active mixed slurry is coated on the carbon coating layer 12, and then dried to form a positive electrode material layer 13;

[0104] After the positive electrode solid electrolyte slurry is coated on the positive electrode material layer 13 , it is dried to form a positive electrode solid electrolyte layer 14 , and the positive electrode sheet 1 is obtained.

[0105] Preferably, step S2 also includes:

[0106] S21, mixing the negative electrode active material containing the composite lithium element 3, the second solid electrolyte, the second conductive agent, the second adhesive, and the second solvent according to a second preset ratio to form a negative electrode active mixed slurry;

[0107] The fourth solid electrolyte, the fourth binder and the fourth solvent are mixed in a fourth predetermined ratio to form a negative electrode solid electrolyte slurry.

[0108] In this step, the order of obtaining the negative electrode active mixed slurry, the negative electrode electrolyte slurry and the order of obtaining the positive electrode active slurry and the positive electrode solid electrolyte slurry is not particular, and the above S1 and S2 do not represent the order of the preparation method.

[0109] Preferably, step S2 further includes:

[0110] S22, coating the negative electrode active mixed slurry containing the composite lithium element 3 on the copper foil 21, and drying it to form the positive electrode material layer 13;

[0111] After the negative electrode solid electrolyte slurry is coated on the positive electrode material layer 13 , it is dried to form a negative electrode solid electrolyte layer 23 , and the negative electrode sheet 2 is obtained.

[0112] Preferably, the drying temperature in step S12 and step S22 is in the range of 60°C to 120°C.

[0113] Preferably, when preparing the positive electrode active mixed slurry and the positive electrode solid electrolyte slurry, as well as the positive electrode solid electrolyte slurry and the negative electrode solid electrolyte slurry, the corresponding materials are placed in a high-speed planetary tank for high dispersion until the size of the dispersed slurry particles is no larger than the maximum size of the dry powder particles of the corresponding material. The size of the dispersed slurry particles is the fineness of the slurry.

[0114] Preferably, steps S1 to S5 are performed under the condition that the dew point is not greater than -35° C. When the dew point is below -35° C., the humidity in the workshop can be ensured to be less than 1%, thereby avoiding the influence of moisture on the battery manufacturing process.

[0115] Preferably, step S4 further includes: S41, the aluminum foil 11 of the positive electrode sheet 1 is electrically connected to the positive electrode tab, and the copper foil 21 of the negative electrode sheet 2 is electrically connected to the negative electrode tab.

[0116] Preferably, the vacuum degree of the battery in step S5 is 0.85 kPa to 85 kPa, and the vacuuming time is 30 s to 120 s. Further preferably, after the liquid electrolyte is injected into the battery in step S5, the lithium ions are solvated in the liquid electrolyte, and a SEI film, i.e., a solid electrolyte interface film, is formed on the surface of the negative electrode material layer to improve the stability and life of the battery.

[0117] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A solid-state lithium-ion battery, characterized in that: include: shell; A positive electrode sheet (1) and a negative electrode sheet (2) are arranged in a wound or stacked manner in the housing; characterized in that: The positive electrode sheet (1) comprises an aluminum foil (11), and a carbon coating layer (12), a positive electrode material layer (13) and a positive electrode solid electrolyte layer (14) are sequentially arranged from the inside to the outside on each side of the aluminum foil (11); The negative electrode sheet (2) comprises a copper foil (21), and a negative electrode material layer (22) and a negative electrode solid electrolyte layer (23) are sequentially arranged from the inside to the outside on each side of the copper foil (21); The negative electrode material layer (22) comprises a negative electrode active material, the negative electrode active material comprises a composite lithium element (3), and the composite lithium element (3) comprises a lithium element layer (31), a lithium carbonate layer (32), a carbon coating layer (33) and a solid electrolyte phase interface film (34) arranged in sequence from the inside to the outside.

2. The solid-state lithium-ion battery according to claim 1, characterized in that: The positive electrode material layer (13) includes a uniformly mixed positive electrode active material and a first solid electrolyte, and the negative electrode material layer (22) also includes a second solid electrolyte; The size range of the particle size D50 of the material particles of the first solid electrolyte and the second solid electrolyte is 0.5 μm to 10 μm; The ratio of the particle size D50 of the material particles of the first solid electrolyte to the particle size D50 of the material particles of the positive electrode active material is in the range of 1:2-1:5; The ratio of the particle size D50 of the material particles of the second solid electrolyte to the particle size D50 of the material particles of the negative electrode active material is in the range of 1:2-1:

5.

3. The solid-state lithium-ion battery according to claim 2, characterized in that: The positive electrode solid electrolyte layer (14) comprises a third solid electrolyte, the negative electrode solid electrolyte layer (23) comprises a fourth solid electrolyte, and the particle size D50 of the material particles of the third solid electrolyte and the fourth solid electrolyte are both in the range of 0.5 μm to 10 μm.

4. The solid-state lithium-ion battery according to claim 3, characterized in that: The porosity of the positive electrode material layer (13), the negative electrode material layer (22), the positive electrode solid electrolyte layer (14) and the negative electrode solid electrolyte layer (23) are all less than 30%.

5. The solid-state lithium-ion battery according to claim 3, characterized in that: The positive electrode material layer (13) further comprises a first conductive agent and a first adhesive, wherein the mass ratio of the positive electrode active material, the first solid electrolyte, the first conductive agent and the first adhesive is in the range of (93wt% to 96wt%): (2wt% to 5wt%): (1wt% to 3wt%): (2wt% to 3wt%); And / or, the negative electrode active material further includes a second conductive agent and a second binder, and the mass ratio of the negative electrode active material, the second solid electrolyte, the second conductive agent and the second binder is (93wt% to 96wt%): (2wt% to 5wt%): (1wt% to 3wt%): (2wt% to 3wt%); And / or, the positive electrode solid electrolyte layer (14) further comprises a third adhesive, and the mass ratio of the third solid electrolyte to the third adhesive is in the range of (95wt% to 98wt%): (2wt% to 5wt%); And / or, the negative electrode solid electrolyte layer (23) further comprises a fourth adhesive, and the mass ratio of the fourth solid electrolyte to the fourth adhesive is in the range of (95wt% to 98wt%): (2wt% to 5wt%).

6. The solid-state lithium-ion battery according to claim 1 or 2, characterized in that: The thickness of the aluminum foil (11) ranges from 10 μm to 13 μm; The thickness of the carbon coating layer (12) ranges from 0.5 μm to 1 μm; The thickness of the positive electrode material layer (13) ranges from 150 μm to 250 μm; The material surface density of the positive electrode material layer (13) is 150 g / ㎡-220 g / ㎡; The thickness of the positive electrode solid electrolyte layer (14) is 5 μm to 10 μm; the thickness of the negative electrode solid electrolyte layer (23) is 5 μm to 10 μm; The NP ratio of the solid-state lithium-ion battery ranges from 1.05 to 1.

15.

7. The solid-state lithium-ion battery according to claim 1 or 2, characterized in that: The positive electrode material layer (13), the negative electrode material layer (22), the positive electrode solid electrolyte layer (14) and the negative electrode solid electrolyte layer (23) all include a liquid electrolyte with a mass ratio of 1-5 wt%.

8. The solid-state lithium-ion battery according to claim 5, characterized in that: The positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich layered oxide; The negative electrode active material also includes at least one of graphite, lithium titanate, silicon carbon, silicon oxygen, hard carbon, and soft carbon; The carbon coating layer (12), the first conductive agent and the second conductive agent include at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fibers and carbon black; The first adhesive, the second adhesive, the third adhesive and the fourth adhesive all include at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyacrylate, nitrile rubber and styrene-butadiene rubber; The positive electrode active material layer further comprises a first solvent, the negative electrode active material layer further comprises a second solvent, the positive electrode solid electrolyte layer (14) further comprises a third solvent, and the negative electrode solid electrolyte layer (23) further comprises a fourth solvent, the first solvent, the third solvent and the fourth solvent are all N-methylpyrrolidone, and the second solvent is deionized water; The first solid electrolyte, the second solid electrolyte, the third solid electrolyte and the fourth solid electrolyte each include at least one of a halide solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte and a polymer electrolyte.

9. A method for preparing a solid-state lithium-ion battery cell, characterized in that: include: S1, coating a carbon material on an aluminum foil (11) to form a carbon coating layer (12); Applying a positive electrode active mixed slurry on the carbon coating layer (12) to form a positive electrode material layer (13); Applying a positive electrode solid electrolyte slurry on the positive electrode material layer (13) to form a positive electrode solid electrolyte layer (14), thereby obtaining a positive electrode sheet (1); S2, coating a negative electrode active mixed slurry containing a composite lithium element (3) on a copper foil (21) to form a negative electrode material layer (22); Applying a negative electrode solid electrolyte slurry on the negative electrode material layer (22) to form a negative electrode solid electrolyte layer (23), and obtaining a negative electrode sheet (2); S3, rolling, slitting, winding or laminating the positive electrode sheet (1) and the negative electrode sheet (2) to form a battery core; S4, the battery cell is installed in a housing to form a battery; S5. Inject liquid electrolyte into the battery, and evacuate the battery and seal it.

10. The method for preparing a solid-state lithium-ion battery cell according to claim 9, characterized in that: The vacuum degree of the battery in S5 is not greater than -85 kPa, and the vacuuming time is 30 s to 120 s.

Citation Information

Cited By

  • Positive plate and preparation method thereof, all-solid-state battery, battery assembly and electric equipment

    CN120261477A

  • Battery cell, battery device and electric device

    CN120565952A